Resource utilization of waste tailings: Simulated removal of nitrogen from secondary effluent by autotrophic denitrification based on pyrite tailings - Mao, Jie; He, Mengqi; Qin, Ying; Chen, You; Wang, Xinyu; Che, Haojie; Cheng, Chun; Wang, Tiantian; Wang, Wenliang; Sun, Bai; Zhu, Shuguang (Frontiers in Environmental Science, 2022)
In this report, environmentally friendly and low-cost pyrite tailings are utilized as denitrification material, while pyrite and magnetite are used as the control experimental group to explore the denitrification performance of pyrite tailings. The results show that the removal effect of pyrite tailings on NO3- is slightly lower than that of pyrite. However, the concentration of NH4+ decreased and the effluent SO42- concentration was lower than that of pyrite. In addition, pyrite with different particle sizes are prepared by ball milling, and the effect of particle size on the denitrification performance of pyrite is studied. The results show that with the decrease in particle size, microorganisms are more likely to use S in tailings as electron donors, the denitrification rate is faster and the denitrification effect was better at the same time.